Migrant trajectories: Venezuelan youth in Peru. Executive summary - Salmón, Elizabeth (2022)
Researchers: Cécile Blouin, Stéphanie Borios, Robin Cavagnoud, Gonzalo Gamio Gheri, Marcela Huaita Alegre, Elizabeth Salmón, Pablo Vega Romá, Crisbeth Vigo